PSIKOEDUKASI PENANGANAN MASALAH EMOSI DAN PERILAKU ANAK USIA DINI - Monika; Ezra Joshua Halim; Jessica Winata (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Early childhood during its development period experiences significant changes in various aspects, including emotional and behavioral aspects. Problems that arise related to emotion and behavior can affect their overall growth and development. In a previous study, 81 children aged 4-10 years were identified through a Strength and Difficulties Questionnaire (SDQ) filled out by parents in Krendang Village, West Jakarta. The results found significant differences between boys and girls. Boys were more often in the abnormal category, especially in the aspects of emotional, behavioral, and social relationship problems, which means that boys are more vulnerable in these categories. While girls fared better, there’s just little difference in terms of percentages between the two genders. The majority of children, both boys and girls, are still in the normal range, but parents still need to pay attention to signs of behavioral and emotional problems in their children. The results of this study were then socialized back to the parents, accompanied by the provision of psychoeducation about handling emotional and behavioral problems in early childhood. The results of this psychoeducation are considered very useful for parents, because through this psychoeducation and dissemination, tips and knowledge about parenting have been given. That way, parents can also understand that proper parenting can help overcome children's emotional and behavioral problems. Early childhood during its development period experiences significant changes in various aspects, including emotional and behavioral aspects. Problems that arise related to emotion and behavior can affect their overall growth and development. In a previous study, 81 children aged 4-10 years were identified through a Strength and Difficulties Questionnaire (SDQ) filled out by parents in Krendang Village, West Jakarta. The results found significant differences between boys and girls. Boys were more often in the abnormal category, especially in the aspects of emotional, behavioral, and social relationship problems, which means that boys are more vulnerable in these categories. While girls fared better, there’s just little difference in terms of percentages between the two genders. The majority of children, both boys and girls, are still in the normal range, but parents still need to pay attention to signs of behavioral and emotional problems in their children. The results of this study were then socialized back to the parents, accompanied by the provision of psychoeducation about handling emotional and behavioral problems in early childhood. The results of this psychoeducation are considered very useful for parents, because through this psychoeducation and dissemination, tips and knowledge about parenting have been given. That way, parents can also understand that proper parenting can help overcome children's emotional and behavioral problems.